La mala fe y la competencia desleal en el registro marcario: análisis comparado a partir de la Decisión 486 - Bassino Pinasco, Manlio (2023)
In this paper, the relationship between unfair competition and intellectual property regulation will be analyzed, focusing on the application of Article 137 of Decision 486. Hence, firstly, bad faith and unfair competition as unregistrability provisions of trademarks will be conceptually analyzed; secondly, the application in Colombia, Ecuador, Bolivia, and Peru in the last years of said Article will be assessed; and, thirdly, the pre-judiciary interpretations issued by the Court of Justice of the Andean Community will be reviewed. Considering the above, it can be concluded and established the "jurisprudential requirements" for the application of Article 137 of Decision 486; as well as, the challenges faced by the owner of an intellectual property right to activate its application.